Work matters : connecting Sunday worship to Monday work - Nelson, Tom, 1956- (Wheaton, Ill. : Crossway, 2011)
"Work. For some this word represents drudgery and the mundane. For others work is an idol to be served. If you find yourself anywhere on the spectrum from workaholic to weekend warrior, it's time to bridge the gap between Sunday worship and Monday work. Striking a balance between theological depth and practical counsel, Tom Nelson outlines God's purposes for work in a way that helps us to make the most of our vocation and to join God in his work in the world. Discover a new perspective on work that will transform your workday and make the majority of your waking hours matter, not only now, but for eternity" -- Publisher description.
Introduction : connecting Sunday to Monday -- Created to work -- Is work a four-letter word? -- The good news of work -- Work now and later -- Extraordinary ordinary work -- The transforming power of work -- Work and the common good -- Gifted for work -- Facing challenges in our work -- The church at work.
Includes bibliographical references (p. 211-213) and indexes.
Keywords: Employees -- Religious life; Work -- Religious aspects -- Christianity